The impact of myeloid derived suppressor cells on vaccine immunogenicity in South African HIV-infected and uninfected mothers and their infants - Kidzeru, Elvis Banboye (Division of Immunology, 2016)
BACKGROUND: Each year over 4 million infants die from infections, of which many are vaccinepreventable. Young infants respond poorly to vaccines, but the basis of reduced immunity is controversial. We hypothesized that myeloid-derived suppressor cells (MDSC) that might be induced during gestation, would persist at birth leading to active suppression of infant-immune responses. OBJECTIVE: We evaluated the ontogeny of MDSC and the effect of MDSC on vaccine immunogenicity during early life in South African infants and mothers, and in HIVexposed uninfected (HEU) infants and HIV+ mothers. METHODS: HIV-infected and uninfected mothers and their infants were recruited from Khayelitsha, Cape Town and followed-up for one year. In whole PBMC and after MDSC (CD15+) depleted, we measured BCG, Hepatitis B, Tetanus toxoid and Bordetella pertussis vaccine-specific CD4+ T cell proliferation by CFSE and IFN-γ responses using ELISpot assay.